Metode Waterfall pada Sistem Informasi Pengolahan Data Penjualan dan Pembelian Barang - Rohmat Rifai; Mely Mailasari (Teknik Informatika Universitas Pamulang, 2020)
Fang Fifi Cell store is one of the shops selling cellphones and accessories in Bekasi. The system used at the Fang Fifi Cell Store is still very manual, starting from data collection, transactions, and reporting. Data collection of goods and transactions still uses handwriting so that recording errors often occur and it is difficult to find data due to accumulation of files. Therefore a problem solving is needed to make it easier for staff to work, namely by making a transaction program and stock goods using the waterfall method, the process is structured and then tested with blackbox testing so thatproduce quality programs that are effective and efficient.This program is expected to support all sales activities and data collection of goods at the Fang Fifi Cell Store as a whole so that it can improve transaction services and inventory data collection as well as making reports.